A recommendation for a pre-standardized marine microalgal dry 3 weight determination protocol for laboratory scale culture using 4 ammonium formate as a washing agent - Khaw, Yam Sim; Tan, Hui Teng; Sopawong, Arissara; Shaharuddin, Noor Azmi; Omar, Abdul Rahman; Md. Yusoff, Fatimah (Multidisciplinary Digital Publishing Institute, 2021)
Microalgal biomass is one of the crucial criteria in microalgal studies. Many reported methods, even the well-established protocol on microalgal dry weight (DW) determination, vary greatly, and reliable comparative assessment amongst published results could be problematic. This study aimed to determine the best condition of critical parameters in marine microalgal DW determination for laboratory-scale culture using four different marine microalgal species. These parameters included the washing process, grades of glass microfiber filter (GMF), GMF pretreatment conditions, washing agent (ammonium formate) concentrations, culture: washing agent ratios (v:v) and washing cycles. GMF grade GF/A with precombustion at 450 °C provided the most satisfactory DW and the highest ash-free dry weight (AFDW)/DW ratio. Furthermore, 0.05 M ammonium formate with 1:2 culture: washing agent ratio and a minimum of two washing cycles appeared to be the best settings of microalgal DW determination. The present treatment increased the AFDW/DW ratio of the four respective microalgae by a minimum of 19%. The findings of this study could serve as a pivotal reference in developing a standardized protocol of marine microalgal DW determination to obtain veracious and reliable marine microalgal DW.